PENGARUH OPINI AUDIT TAHUN SEBELUMNYA DAN FINANCIAL DISTRESS TERHADAP OPINI AUDIT GOING CONCERN - MUYASSAROH -; AKHMAD SIGIT ADIWIBOWO (STIE Indonesia Malang, 2023)
This study aims to determine the effect of the Previous Year's Audit Opinion and Financial Distress on the Going Concern Audit Opinion. The previous year's audit opinion was measured using a dummy variable. Financial distress is measured using the Altman z-score. While the going concern audit opinion is measured using a dummy variable. The population in this study are all financing service sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The number of samples in this study were 15 companies obtained through the purposive sampling method, so that 70 sample data were obtained. The type of data in this study is secondary data with quantitative research methods. The analysis technique used is logistic regression analysis. This research was processed using eviews 9 software and showed that (1) the previous year's audit opinion partially influenced the going concern audit opinion. (2) Financial distress does not partially affect the going concern audit opinion. (3) The previous year's audit opinion and financial distress simultaneously influence the going concern audit opinion.Keywords : Previous Year Audit Opinion, Financial Distress, Audit Opinion Going Concern